Development of calcium-based metal-organic frameworks as fungicides carrier agents against Ganoderma boninense - Ahmad Aljafree, Nurul Farhana (2023)
Fungicides are crucial for defending against major plant pathogens that cause severe diseases to plants. Fungal diseases such as basal stem rot (BSR) caused by Ganoderma spp. fungi have affected one of the most important commodities in Malaysia. Most of the fungicide active ingredients are not stable which required them to be formulated with inert ingredients such as organic solvents. The application of these organic solvents contributed to the environmental problem as there is no control in the release rate of the fungicide active ingredients. Increasing attention to improving fungicide stability is believed to be helpful in preventing environmental degradation and ecological issues. One of the methods for reducing the amount of fungicide usage while maintaining its effectiveness is through the incorporation of carrier agents in sustaining the delivery system for an extended time. The objective of this study is to develop calcium-based metal-organic framework as slowreleased fungicide carrier agents against Ganoderma boninense. In this study, plant acid linkers, namely, L-lactic, L-malic, and D-tartaric were used to construct calcium-based metal‒organic frameworks (MOFs). L-Lactic, L-malic, and D-tartaric acids are naturally occurring compounds found in citrus fruits, making them safe and environmentally friendly for biological and environmental applications. The crystal structures of MOF- 1201, UPMOF-1, and UPMOF-2 were determined by single-crystal X-ray diffraction (SCXRD) analysis and fully characterized by powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), Fourier-transform infrared (FTIR) spectroscopy, elemental analysis, field emission scanning electron microscope (FESEM), and energy dispersive X-ray (EDX) microscopy. MOF-1201, UPMOF-1 and UPMOF-2 are threedimensional networks and crystallize in monoclinic and orthorhombic lattice systems. Both UPMOF-1 and UPMOF-2 are novel MOFs where UPMOF-1 exhibits a new topology, and UPMOF-2 possesses gra topology. Hexaconazole, a systemic fungicide from triazole group was incorporated in calcium-based metal-organic frameworks using a microwave irradiation technique. The loading content of hexaconazole in MOF-1201, UPMOF-1, and UPMOF-2 was determined using High-Performance Liquid Chromatography (HPLC). From the results, Hexa-MF, Hexa-UP1, and Hexa-UP2 were abled to maintain their crystallinity with high encapsulation efficiency (EE) values more than 80.0%. Hexa-MOFs loaded with different amount of hexaconazole were used as effective antifungal agents against G. boninense. Hexa-MOFs effectiveness were evaluated via artificial inoculation of oil palm seedlings with the rubber woodblock, which fully colonized with the G. boninense mycelium. The highest disease reduction of 100.0% was obtained from Hexa-UP1 loaded with 3.0% hexaconazole at 26 weeks after inoculation (WAI). This study provides a potential in the development of efficient carrier agents that are capable to sustain the active ingredient for a longer period.